Folate-Dependent Cognitive Impairment Associated With Specific Gene Networks in the Adult Mouse Hippocampus - Lawton, Abigail; Morgan, Caroline R.; Schreiner, Caleb R.; Schreiner, Chris G.; Baumann, Jacqueline; Upchurch, Britton; Xu, Feifan; Price, Michael S.; Isaacs, Gary D. (Frontiers in Nutrition, 2020)
Short-term folate deficiency has been linked to cognitive defects. Given folate’s role in regulating nucleotide synthesis and DNA and histone methylation, these changes are often linked to altered gene expression and might be controlled by specific regulatory networks. In our study we examined the effects of folic acid deficient or replete diets in mice, containing either no source of folate or normal folic acid intake, beginning post-weaning and persisting through the end of adult life at 18 mos. Our goal was to assess levels of cognition in these mice using the novel object test and then connect the cognitive results to genetic changes. Folic acid deficient mice showed significant memory impairment compared to control counterparts beginning at 5 mo and persisting through 17 mo, as determined by the novel object test. These deficits were associated with 363 significantly downregulated and 101 significantly upregulated genes in the deficient condition compared to the control condition in microarray analysis of hippocampal tissue. Many of these gene expression changes were determined to be specific to the hippocampus. Significant ontological categories for differential genes included nucleotide regulation, ion channel activity, and MAPK signaling; while some of these categories contain genes previously mapped to cognitive decline, other genes have not previously been associated with cognition. To determine proteins possibly involved in regulation of these genes, we performed bioinformatics analysis and found enriched motifs of for MafB and Zfp410 binding sites. These genes and enriched motifs may represent targets for treatment or investigation of memory-related diseases.